STRATEGI PROMOSI DIGITAL MELALUI PENDEKATAN AIDA (STUDI KASUS PADA CLUB MALAM AFTERHOUR BALI) - Wijaya, Garda Patria; Arjaya, Ketut; Sana, I Nyoman Lingga (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This study was conducted at Afterhour Bali and explores the effectiveness of event promotion through Instagram in increasing visitor attendance at the Afterhour Bali nightclub. A qualitative descriptive method was employed, with data collected through interviews, observations, and document analysis. The data were analyzed using the AIDA model to assess promotional strategies and the utilization of Instagram features. The findings indicate that Afterhour Bali’s promotional strategies are relatively effective, particularly through the use of Instagram features such as Feed Posts, Reels, Stories, Ads, Captions, and Highlights. Furthermore, when analyzed through the AIDA framework, it was found that Afterhour Bali not only relies on these features but also implements a structured promotional approach, including content planning, publication, and performance evaluation based on Instagram analytics.